The Implementation of Authentic Assessment in Thematic Learning in Elementary Schools - Safitri, Debby Intan; Mudzanata, Mudzanata; Setya Putri, Anggun Dewi (Universitas Pendidikan Ganesha, 2020)
The purpose of this study was to determine the teacher's pedagogical competence in the implementation of authentic assessment in the thematic learning of the second grade in SD Negeri (Public Elementary School) Pandeanlamper 01 Semarang. The background was due to teacher difficulty in implementing authentic assessments. The type of study was qualitative research. Data in this study were obtained through observation, interviews, and documentation. The results of this study indicate that 1) teachers and principals know about authentic assessments in thematic learning 2) teachers carry out authentic assessments that include assessment of competency attitudes, knowledge, and skills. The attitude competency assessment was conducted through a journal assessment. Knowledge competency assessment was conducted through written tests and assignment techniques. Skill competency assessment was conducted through product assessment techniques.